Mathematics Teachers' Learning Through Inquiry - Olive Chapman (Universidade de Lisboa, 2013)
Inquiry-based teaching strives to engage students in learning mathematics with understanding in the classroom. Therefore, there is great interest in supporting teachers to meet this pedagogical challenge by developing practices that promote such an educational environment at different school levels. A powerful way for teachers to learn and transform their teaching is through teacher inquiry. This paper presents a model for inquiry into mathematics teaching based on the perspectives of theorists directly associated with teacher education. This model is described as an overarching inquiry cycle in which teachers begin with practice, pose a pedagogical problem, understand a key construct in the problem, hypothesize an inquiry-teaching model, test/apply it, and finally revise/apply this model. This approach is illustrated with a self-directed professional development process aimed at helping elementary teachers to develop understanding of inquiry-based teaching of mathematics.